2020
DOI: 10.1128/ecosalplus.esp-0025-2019
|View full text |Cite
|
Sign up to set email alerts
|

Prokaryotic Organelles: Bacterial Microcompartments in E. coli and Salmonella

Abstract: Bacterial microcompartments (MCPs) are proteinaceous organelles consisting of a metabolic pathway encapsulated within a selectively permeable protein shell. Hundreds of species of bacteria produce MCPs of at least nine different types, and MCP metabolism is associated with enteric pathogenesis, cancer, and heart disease. This review focuses chiefly on the four types of catabolic MCPs (metabolosomes) found in Escherichia coli and Salmonella : the propanediol utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 216 publications
(522 reference statements)
0
19
0
Order By: Relevance
“…According to current models, EA is catabolized to acetate and ethanol in a molar ratio of 1:1 via the oxidative ATP-producing branch and reductive NAD + -regenerating branch ( 6 ). Interestingly, previous studies showed that EA confers a marked anaerobic growth advantage on Salmonella enterica serovar Typhimurium only in the presence of tetrathionate, acting as an alternative electron acceptor via tetrathionate reductase ( 6 , 14 16 ), and the mutant lacking the tetrathionate reductase showed a decreasing colonization capacity in a mouse colitis model, which points to a role for anaerobic electron transfer in EA catabolism contributing to the growth of S. enterica in the lumen of the inflamed intestine ( 15 ). Anaerobic EA catabolism in L. monocytogenes , including possible roles for anaerobic respiration, has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…According to current models, EA is catabolized to acetate and ethanol in a molar ratio of 1:1 via the oxidative ATP-producing branch and reductive NAD + -regenerating branch ( 6 ). Interestingly, previous studies showed that EA confers a marked anaerobic growth advantage on Salmonella enterica serovar Typhimurium only in the presence of tetrathionate, acting as an alternative electron acceptor via tetrathionate reductase ( 6 , 14 16 ), and the mutant lacking the tetrathionate reductase showed a decreasing colonization capacity in a mouse colitis model, which points to a role for anaerobic electron transfer in EA catabolism contributing to the growth of S. enterica in the lumen of the inflamed intestine ( 15 ). Anaerobic EA catabolism in L. monocytogenes , including possible roles for anaerobic respiration, has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reviews have delved into a wide variety of topics such as BMC positioning [5], BMC repurposing for industrial uses [6], evolutionary relationship of shell proteins across different BMCs [7], and BMC protein stoichiometry [8,9]. [10][11][12][13]. The charge of each metabolite is indicated with color; positive in red, negative in blue, and neutral in grey.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1. Diagram of the substrates, intermediates, and products of carboxysomes and the most studied catabolic BMCs[10][11][12][13]. The charge of each metabolite is indicated with color; positive in red, negative in blue, and neutral in grey.…”
mentioning
confidence: 99%
“…One of the most well-studied types of metabolosomes is the 1,2-propanediol utilization (Pdu) MCP found in Salmonella enterica serovar Typhimurium LT2 (hereafter referred to as "LT2"). The Pdu MCP provides an excellent model for metabolosome 5 study as Pdu MCPs natively exist in a number of model bacterial hosts such as the aforementioned LT2 as well as strains of Escherichia coli (11). Pdu MCPs are broadly distributed throughout many bacterial phyla and numerous Pdu subtypes exist (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%